Penggunaan Media Papan Flanel dan Kartu Kata pada Kemampuan Membaca Anak Usia Dini - Uswatun, Uswatun; Suryani, Lilis (Universitas Muhammadiyah Ponorogo, 2025)
This study aims to explore the use of flannel board media and word cards in developing early childhood reading skills at IT HASMI Kindergarten, Tamansari District, Bogor. The method used is a descriptive qualitative approach, which focuses on direct observation of the learning process. Data were collected through observation, interviews, and documentation studies, and analyzed with a descriptive approach. The results showed that the use of flannel board and word card media has a positive impact in increasing children's learning engagement and enthusiasm. This media allows children to learn interactively, so they are more active in asking, answering and solving problems. In addition, flannelboard and word card media help children recognize letters, syllables and words in a fun way, thus improving their reading skills. Despite some shortcomings, such as the limited capacity of the flannel board and the risk of damage to the word cards, this study found that both media can be used effectively in learning to read. Teachers at HASMI Kindergarten plan the use of these media carefully, considering the material being taught and the activities that support children's active participation. The study concludes that the use of flannel board and word card media not only improves children's reading skills, but also creates a fun and interactive learning atmosphere. Thus, this study makes an important contribution in the development of effective learning methods for early childhood, as well as being a reference for educators in designing more interesting and useful learning activities.